IMPROVEMENT OF MARKETING IN THE ACTIVITY OF TOUR OPERATORS IN UZBEKISTAN (Marketing Journal, 2025)
The 21st century has entered social life as the age of information. The exchange of information between countries has accelerated significantly, and economic development over the last two decades has been several times faster than in previous years. This r apid development has also had an impact on the tourism sector. By applying technological innovations in the tourism industry, leading countries are achieving high revenues. In the current era of globalization, tour operator organizations cannot achieve any significant progress without mutual integration. The development of tour operator activities plays a leading role in expanding tourism opportunities in our country, just as in other sectors of the economy. The deve lopment of a modern tourism industry in Uzbekistan that can adapt to rapid global changes is of great importance, and private sector entities play a crucial role in this process. The main goal of these reforms is to effectively utilize the developed tourism industry to stabilize mutual social and economic relations between our independent country and the rest of the world. This case study aims to analyze the changes in the tourism sector of our country and examine the modern operations of tour operator firms that positively influence the motivation of visiting tourists. The study employs a qualitative research method, collecting data through interviews with 30 international tourists who have visited our country.
Keywords: tour operator; travel agent; tour itinerary; tourism resources; accommodation facilities; transport characteristics; motivation; tourist; travel